The secret of the highly creative thinker : how to make connections others don't - Nielsen, Dorte, 1967-; Thurber, Sarah, ....- (Amsterdam, The Netherlands : BIS Publishers, 2020)
People who are good at creating ideas are good at seeing connections. Could teaching people to see connections be a way to help them be more creative?Over the years, there's a need for a book on creativity that complements the teaching of the creative process and tools and gives you a practical approach to how to enhance your innate ability to think creatively. This book as an opportunity to dispel the myth that creative talent is something possessed by a gifted minority. This is the opportunity to pass on 'the secret' of highly creative people to a much wider audience. It's a chance to give others the knowledge, techniques, and training they need to enhance their own innate creativity and lead the way to fun, fulfillment, invention, innovation, and change.It's a unique book that combines a very hands on and practical approach with a solid scholarly foundation.
Includes bibliographical references (pages 178-181)
Keywords: Creativiteit; Neurowetenschappen